M2 macrophage-derived TGF-β induces age-associated loss of adipogenesis through progenitor cell senescence - Xinyi Zeng; Teh-Wei Wang; Kiyoshi Yamaguchi; Seira Hatakeyama; Satoshi Yamazaki; Eigo Shimizu; Seiya Imoto; Yoichi Furukawa; Yoshikazu Johmura; Makoto Nakanishi (Elsevier, 2024)
Objectives: Adipose tissue is an endocrine and energy storage organ composed of several different cell types, including mature adipocytes, stromal cells, endothelial cells, and a variety of immune cells. Adipose tissue aging contributes to the pathogenesis of metabolic dysfunction and is likely induced by crosstalk between adipose progenitor cells (APCs) and immune cells, but the underlying molecular mechanisms remain largely unknown. In this study, we revealed the biological role of p16high senescent APCs, and investigated the crosstalk between each cell type in the aged white adipose tissue. Methods: We performed the single-cell RNA sequencing (scRNA-seq) analysis on the p16high adipose cells sorted from aged p16-CreERT2/Rosa26-LSL-tdTomato mice. We also performed the time serial analysis on the age-dependent bulk RNA-seq datasets of human and mouse white adipose tissues to infer the transcriptome alteration of adipogenic potential within aging. Results: We show that M2 macrophage-derived TGF-β induces APCs senescence which impairs adipogenesis in vivo. p16high senescent APCs increase with age and show loss of adipogenic potential. The ligand-receptor interaction analysis reveals that M2 macrophages are the donors for TGF-β and the senescent APCs are the recipients. Indeed, treatment of APCs with TGF-β1 induces senescent phenotypes through mitochondrial ROS-mediated DNA damage in vitro. TGF-β1 injection into gonadal white adipose tissue (gWAT) suppresses adipogenic potential and induces fibrotic genes as well as p16 in APCs. A gWAT atrophy is observed in cancer cachexia by APCs senescence, whose induction appeared to be independent of TGF-β induction. Conclusions: Our results suggest that M2 macrophage-derived TGF-β induces age-related lipodystrophy by APCs senescence. The TGF-β treatment induced DNA damage, mitochondrial ROS, and finally cellular senescence in APCs.